2022
DOI: 10.4235/agmr.21.0138
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Eccentric Exercise to Improve Muscle and Mobility Function in Older Adults

Abstract: Muscle aging ultimately leads to the deterioration of human physiological functioning, including declining muscle strength, loss of muscle mass, and decreased quality of life in advanced age.Eccentric exercise is a key intervention that has the potential to ameliorate this problem. Recent studies have focused on evidence-based exercise interventions to prevent declines in muscle strength and physical function in older adults. This paper reviewed relevant literature on the use of eccentric exercise to improve m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
(158 reference statements)
0
4
0
Order By: Relevance
“…[34,35] These short-term changes and long-term resistance training can improve efficiency of mitochondria and muscle protein synthesis-breakdown mechanisms, playing a vital role in maintaining muscle mass and muscle function. [36,37] In addition to increasing muscle mass, physical activity, including resistance exercise, can independently enhance muscle function. [30] For example, remodeling of neuromuscular junctions can improve motor unit recruitment even in the absence of increased muscle mass, leading to improved muscle function.…”
Section: Neuro-mechanical Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34,35] These short-term changes and long-term resistance training can improve efficiency of mitochondria and muscle protein synthesis-breakdown mechanisms, playing a vital role in maintaining muscle mass and muscle function. [36,37] In addition to increasing muscle mass, physical activity, including resistance exercise, can independently enhance muscle function. [30] For example, remodeling of neuromuscular junctions can improve motor unit recruitment even in the absence of increased muscle mass, leading to improved muscle function.…”
Section: Neuro-mechanical Factorsmentioning
confidence: 99%
“…While most of the studies on effective exercise intervention studies have not targeted older populations diagnosed with sarcopenia, structured exercise may potentially improve parameters such as muscle strength, walking speed, and simple physical function in populations with concurrent sarcopenia. [30,36] Additionally, further studies are warranted to ascertain how exercise can prevent disability and maintain activities of daily living. Exercise programs aimed at improving accessibility in the metaverse have been explored recently; however, additional validation studies are required for further assessment.…”
Section: Exercisementioning
confidence: 99%
“…Since active muscle volume theoretically determines energy expenditure (6), the neuromuscular efficiency of eccentric contractions is therefore increased (7,8). As eccentric contractions require less energy and muscle activity for equivalent force production, eccentric exercise has received considerable attention over the last decades to rehabilitate injuries, to improve athletic performance, and to help manage neuromuscular diseases (9)(10)(11)(12)(13). Accordingly, many training studies aimed to determine the specific adaptations of the muscle-tendon unit (MTU) to eccentric exercise in comparison to concentric exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some studies reported lower or minimal cardiorespiratory load evoked by eccentric exercise, which could be an advantage when applied for older individuals. Another aspect that needs to be considered before the application of eccentric exercise is delayed onset of muscle soreness (DOMS), which is usually manifested by pain, swelling, stiffness, and structural damage caused by eccentric contractions [ 46 ]. However, some authors have suggested that this phenomenon occurs less in older individuals.…”
Section: Introductionmentioning
confidence: 99%